Trust and communication influence on farm performance for paddy farmers: a study in Bangladesh - Iris, Farhana; Mohd Nawi, Nolila; Man, Norsida; Ramli, Nurul Nadia; Uddin, Md. Taj (Asian Economic and Social Society, 2022)
Farmers are currently moving toward business relationships and forming close ties with business partners in the supply chain. Close business ties reduce costs, enhance efficiency, improve profit, increase competitive advantage and build personal relationships. Utilizing strategic relationship elements such as trust and communication has significant importance for farmers and marketers. This study assessed the influence of trust and communication on farm performance of paddy farmers’ in Bangladesh. Data was collected through quantitative survey-based interviews with 356 farmers from the Mymensingh District, Bangladesh. Descriptive analysis was used to summarize the farmers’ demographic details and exchange relationship with their preferred paddy buyer. Partial least squares structural equation modeling (PLS-SEM) was used to test the hypotheses. The findings revealed that trust and communication contributed to promoting paddy farmers’ farm performance, especially profit, sales, and cash flow growth. The study findings offer farmers a basis for developing long-term business relationships by applying trust and communication to establish, maintain, and enhance farm performance.